Emergency centre reorganization in preparation to the COVID-19 pandemic: A district hospital's dynamic adaptation response - Phillip P. Furstenburg; Suzan N. Mukonkole; Crispin N. Kibamba; Ashley Kuiler; Nondumiso Ngemntu; Sa'ad Lahri; Daniël J. van Hoving; Kitesh Moodley; Elaine Erasmus (AOSIS, 2020)
The COVID-19 global pandemic forced healthcare facilities to put special isolation measures in place to limit nosocomial transmission. Cohorting is such a measure and refers to placing infected patients (or under investigation) together in a designated area. This report describes the physical reorganisation of the emergency centre at Khayelitsha Hospital, a district level hospital in Cape Town, South Africa in preparation to the COVID-19 pandemic. The preparation included the identification of a person under investigation (PUI) room, converting short stay wards into COVID-19 isolation areas, and relocating the paediatric section to an area outside the emergency centre. Finally, we had to divide the emergency centre into a respiratory and non-respiratory side by utilising part of the hospital's main reception. We are positive that the preparation and reorganization of the emergency centre will limit nosocomial transmission during the expected COVID-19 surge. Our experience in adapting to COVID-19 may have useful implications for ECs throughout South Africa and in low-and-middle income countries that are preparing for this pandemic.